Civil Servant Competency Development at the Human Resources Development and Personnel Agency - Hertati, Hertati; Samad, Abdul; Mujahid, Mujahid (Newinera Publisher, 2023)
This study aims to determine and analyze the strategies carried out by the Head of BKPSDM and his staff in developing civil servant competencies along with supporting and inhibiting factors. The study was conducted at BKPSDM Nunukan Regency. Data collection was carried out through observation, interviews and documentation. The data were analyzed using qualitative descriptive analysis. Strategies in developing civil servant competencies are very necessary, especially in increasing the achievement of competency development rights for each civil servant. Based on the results of this study, it is known that there are still several deficiencies in the competency development planning process, including the absence of a competency development plan in accordance with the provisions, as well as an evaluation of the implementation of competency development. However, there are several steps taken in implementing competencies that have a significant impact on the achievement of fulfilling the right to develop competencies of 20 teaching hours each year.